Adenophora Stricta Root Extract Protects Lung Injury from Exposure to Particulate Matter 2.5 in Mice - Seok-Man Park; Cheol-Jong Jung; Dae-Geon Lee; Beom-Rak Choi; Tae-Hun Ku; Im-Joung La; Il-Je Cho; Sae-Kwang Ku (MDPI AG, 2022)
Chronic exposure of particulate matter of less than 2.5 μm (PM2.5) has been considered as one of the major etiologies for various respiratory diseases. Adenophora stricta Miq. is a medicinal herb that has been used for treating respiratory diseases in East Asia. The present study investigated the effect of A. stricta root extract (AsE) on PM2.5-induced lung injury in mice. Oral administration of 100-400 mg/kg AsE for 10 days significantly reduced the PM2.5-mediated increase in relative lung weight, but there was no difference in body weight with AsE administration. In addition, AsE dose-dependently decreased congested region of the lung tissue, prevented apoptosis and matrix degradation, and alleviated mucus stasis induced by PM2.5. Moreover, cytological analysis of bronchioalveolar lavage fluid revealed that AsE significantly inhibited the infiltration of immune cells into the lungs. Consistently, AsE also decreased expression of proinflammatory cytokines and chemokines in lung tissue. Furthermore, AsE administration blocked reactive oxygen species production and lipid peroxidation through attenuating the PM2.5-dependent reduction of antioxidant defense system in the lungs. Therefore, A. stricta root would be a promising candidate for protecting lung tissue from air pollution such as PM2.5.